Analyzing Pharoah’s Misleading Discourse in the Holy Quran - Abbas, Haider Fadhil (Al-Adab Journal, 2020)
Analyzing the authoritarian discourse in the Holy Quran uncovers the invisible aspect of language and shows the unconscious response to the power of its hidden patterns. Linguistic adaptation involves an intellectual and ideological adaptation as the mind responds to its linguistic thinking mechanisms. If reality precedes language and language follows it, then language, with all its power and influence over the unconscious, forms this reality as if it precedes rather than follows it. The fact that a given people suffer under the power of brutal suppression by a dictatorship for a long time leads to the production of another suppressive power, i.e. the collective unconscious power which creates a split in the individual personality and entrenches the values of slavery and its patterns. The suppressive legacy is so deep-rooted in Pharoah’s kingdom to the extent that it became its collective memory. Over time, the more this legacy permeates throughout the structure of society, the more it becomes a part of the nation’s identity, and thus becomes sacred. The fact that the Israeli people suffered under the power of cruel repression in Pharoah’s kingdom for a long time led to the production of another suppressive power, i.e. the collective unconscious power which created a split in the individual Israeli personality and entrenched in him the values of slavery and surrender to its patterns. Due to its severity and long duration, the feeling of being under suppression inside the conscious area creates a power of suppression and monitoring inside the unconscious. This leads the personality to create an internal repressive monitor so that a human cannot practice his own human essence under its control; and therefore his will remains paralyzed and searching for a landmark event at a historic moment that brings a new vision that saves this human being from producing his slavery which tyranny forces him to re-produce time after time.